Extra-Oral Taste Receptors—Function, Disease, and Perspectives - Behrens, Maik; Lang, Tatjana (Frontiers in Nutrition, 2022)
Taste perception is crucial for the critical evaluation of food constituents in human and other vertebrates. The five basic taste qualities salty, sour, sweet, umami (in humans mainly the taste of L-glutamic acid) and bitter provide important information on the energy content, the concentration of electrolytes and the presence of potentially harmful components in food items. Detection of the various taste stimuli is facilitated by specialized receptor proteins that are expressed in taste buds distributed on the tongue and the oral cavity. Whereas salty and sour receptors represent ion channels, the receptors for sweet, umami and bitter belong to the G protein-coupled receptor superfamily. In particular, the G protein-coupled taste receptors have been located in a growing number of tissues outside the oral cavity, where they mediate important processes. This article will provide a brief introduction into the human taste perception, the corresponding receptive molecules and their signal transduction. Then, we will focus on taste receptors in the gastrointestinal tract, which participate in a variety of processes including the regulation of metabolic functions, hunger/satiety regulation as well as in digestion and pathogen defense reactions. These important non-gustatory functions suggest that complex selective forces have contributed to shape taste receptors during evolution.